PRO-ACTIVE LEGISLATIVE TARGETS 1990 (900000). PRO-ACTIVE PROPOSAL. OKLAHOMA HIRING DISCRIMINATION (Tufts Archival Research Center, 2007)
Report discussing a pro-active proposal in Oklahoma regarding hiring discrimination. Specifies the tobacco industry's course of action for the piece of legislation. Identifies resources needed to pass legislation favorable for the tobacco industry, including: economic analysis, expert witnesses, coalition allies, Tobacco Institute grassroots mobilization, and company resources. Focuses on lobbying as an essential tactic.